Diversity and distribution of Ischnomesidae (Crustacea: Isopoda: Asellota) along the Kuril-Kamchatka Trench – A genetic perspective. (November 2019) - Bober, Johanna; Brandt, Angelika; Frutos, Inmaculada; Schwentner, Martin
Highlights: High diversity with 24–45 putative species delimited. Most putative species restricted to single sampled area. Hadal species tend to be geographically wider distributed than abyssal species. The Kuril-Kamchatka Trench is an isolation barrier for abyssal Ischnomesidae. Abstract: The aim of this study was to investigate the diversity and distribution of the asellote isopod family Ischnomesidae in the hadal and abyssal of the Kuril-Kamchatka Trench (KKT) and adjacent Sea of Okhotsk and the neighboring northwest Pacific Basin. Ischnomesids were sampled during two expeditions (SokhoBio & KuramBio II) in depths between 3299 and 9584 m. Subsequent to morphological identifications, mitochondrial COI was successfully sequenced for 208 of the 298 sampled specimens. Based on two computational approaches (ABGD and GMYC) 24–45 putative species (lineages) could be delimited. The initially 21 defined morphospecies matched poorly with these COI lineages, in particularly females and juveniles were differently assigned. Fortimesus Kavanagh and Wilson, 2007 was found to be the most abundant and diverse genus, in particular in the hadal. The hadal of the KKT had a higher species diversity (6–9 species) than the adjacent Sea of Okhotsk (1 species), but lower diversity than the abyssal northwest Pacific Basin (15–24 species). Most species were restricted to a single studied area, wider distributions of 300 km were mainly observed for hadal species within the KKT and only to a lesser degree for abyssal species. Species distributions across the KKT were rare and again predominately observed for hadal species. The abyssal species were either restricted to one side of the KKT or the genetic distances between populations on the opposite sides of the KKT were very high. This implies that the KKT serves as an isolation barrier for poorly dispersing benthic species like the herein studied Ischnomesidae.